Detecting Cognitive Decline and Dementia in Santa Cruz, Galápagos Islands, Ecuador - Espinosa del Pozo, Patricio H (Cureus, 2020)
Objective To assess the cognitive function, prevalence, and risk factors associated with cognitive decline and dementia in people above 65 years of age in Santa Cruz Island, Galápagos, Ecuador.  Methods This is a cross-sectional observational study that was carried out in adults over 65 years of age in Santa Cruz Island, Galápagos, Ecuador. The mini-mental state examination (MMSE) and ascertain dementia eight-item informant questionnaire (AD8)-validated Ecuador Spanish versions were used to assess cognition. Results There were a total of 80 participants, 55 (67%) women and 25 (31.2%) men. The majority of participants were Mestizos (85.3%), with the remainder classified as White (4.8%), Afro-Ecuadorians (2.4%), or Indigenous (3.6%). The prevalence of cognitive impairment is 30.0%-43.7%. The MMSE results showed that older age and lack of education are risk factors for cognitive decline (p < 0.01). There was high correlation between MMSE and AD8 scores. The AD8 showed that older age, widowhood, and living in Santa Rosa were risk factors for cognitive decline (p < 0.01). According to the AD8, the group with the highest education (six years or more) had the lowest risk of cognitive decline and dementia (p < 0.01).  Conclusions The main risk factors for cognitive decline and dementia in individuals above 65 years old in Santa Cruz Island, Galápagos, Ecuador are increased age, lack of education, and widowhood. The prevalence of cognitive impairment is similar to previous studies in Ecuador.